ASSESSING THE QUALITY OF LIFE OF THE ELDERLY IN SELECTED REGIONS KELURAHAN TERBAN, YOGYAKARTA, INDONESIA - Melati, Nimsi (Jurnal Kesehatan, 2017)
Background: Indonesia is the third biggest Asian country with a total population aged 60 years and older population after China and India. Based on data from the year 2012 Susesnas Indonesia, elderly population distribution by province shows that the 13.04% of elderly living in Yogyakarta. The elderly need support to face the live changes to maintain high quality of life. Health care provider, family and community around older people should work hand in hand to be support system for our elderly. Objective: to explore about elderly quality of life and ï¬ nd out if there is a signiï¬ cant difference in the self-assessed quality of life of the elderly respondents when their personal proï¬ le characteristics are taken as test factors. Method: This study uses descriptive correlational design. The population are 95 elderly who live in in RW 5 and RW 10 Kelurahan Terban, Yogyakarta. Their quality of life was assessed by themselves and tested by T-test and Anova. Result: Majority of the respondents are 60-70 years old (63%), female (63%), and living with their signiï¬ cant other (78%). There is no signiï¬ cant difference in the self-assessed quality of life of the elderly respondents when their personal proï¬ le (age (F value of 1.849514) and gender (T value of 0.5085)) characteristics are taken as test factors. On other hand, there is a signiï¬ cant difference in the self-assessed quality of life of the elderly respondents when their personal proï¬ le characteristics (living condition) (T value of 2.0972) is taken as test factor. Conclusion: The quality of life of the elderly are good and the living condition has signiï¬ cant difference in self-assessed quality of life of the elderly respondents. Recommendations: There are inputs for enhancement health care service program especially additional activities in Posyandu Lansia.Keywords: Elderly - Quality of Life â€“ PosyanduABSTRAKLatar belakang: Indonesia adalah negara ketiga terbesar yang memiliki populasi lanjut usia (lansia) usia 60 tahun keatas setelah Cina dan India. Berdasarkan data Susenas Indonesia tahun 2012, distribusi populasi lansia berdasarkan provinsi menunjukkan bahwa 13.04% lansia tinggal di Yogyakarta. Lansia memerlukan dukungan untuk menghadapi perubahan kehidupan untuk mempertahankan qualitas hidupnya. Penyedia layanan kesehatan, keluarga dan komunitas disekitar lansiaa harus bekerja sama untuk menjadi pendukung bagi para lansia kita. Tujuan: Mengetahui tentang kualitas hidup lansia dan mengetahui adanya perbedaan signiï¬ kan qualitas hidup dengan karakteristik lansia. Metode: Penelitian ini menggunakan dekriptif korelasi. Populasi penelitian ini adalah 95 lansia yang tinggal di RW 5 dan RW 10 Kelurahan Terban, Yogyakarta. Kualitas hidup lansia diukur oleh lansia sendiri dan diuji dengan T-tes dan Anova. Hasil: Mayoritas response berusia 60-70 tahun (63%), wanita (63%), dan tinggal bersama keluarga (78%). Tidak ada perbedaan signiï¬ kan antara qualitas hidup lansia dengan usia (F value 1.849514) dan jenis kelamin (T value 0.5085). Di sisi lain, ada perbedaan signiï¬ kan antara kualitas hidup lansia dengan kondisi hidup (T value 2.0972). Kesimpulan: Kualitas hidup lansia baik dan kondisi hidup memiliki perbedaan signiï¬ kan dengan kualitas hidup lansia. Saran: Beberapa masukan di berikan untuk meningkatkan program pelayanan kesehatan terutama kegiatan tambahan di Posyandu Lansia. Kata kunci: Lansia-Kualitas Hidup- Posyandu